Ga-68-FAPI PET/CT: biodistribution and preliminary dosimetry estimate of 2 DOTA-containing FAP-targeting agents in patients with various cancers - Giesel, Frederik L.; Kratochwil, Clemens; Lindner, Thomas; Marschalek, Manfred M.; Loktev, Anastasia; Debus, Jürgen; Jäger, Dirk; Flechsig, Paul; Altmann, Annette; Mier, Walter; Haberkorn, Uwe (Journal of nuclear medicine, 2019)
Fibroblast activation protein (FAP) is overexpressed in cancer-associated fibroblasts of several tumor entities. The recent development of quinoline-based PET tracers that act as FAP inhibitors (FAPIs) demonstrated promising results preclinically and already in a few clinical cases. Consequently, these tracers are now applied in our hospital to amend the diagnostics of cancer patients facing the limitations of standard examinations. Here, we analyze the tissue biodistribution and preliminary dosimetry of 2 members of this new class of PET radiopharmaceutical. Methods: A preliminary dosimetry estimate for Ga-68-FAPI-2 and Ga-68-FAPI-4 was based on 2 patients examined at 0.2, 1, and 3 h after tracer injection using the QDOSE dosimetry software suit. Further PET/CT scans of tumor patients were acquired 1 h after injection of either Ga-68-FAPI-2 (n = 25) or Ga-68-FAPI-4 (n = 25); for 6 patients an intraindividual related F-18-FDG scan (also acquired 1 h after injection) was available. For the normal tissue of 16 organs, a 2-cm spheric volume of interest was placed in the parenchyma; for tumor lesions, a threshold-segmented volume of interest was used to quantify SUVmean and SUVmax Results: Similar to literature values for F-18-FDG, Ga-68-DOTATATE, and Ga-68-PSMA-11, an examination with 200 MBq of Ga-68-FAPI-2 or Ga-68-FAPI-4 corresponds to an equivalent dose of approximately 3-4 mSv. After a fast clearance via the kidneys, the normal organs showed a low tracer uptake with only minimal changes between 10 min and 3 h after injection. In Ga-68-FAPI-2, the tumor uptake from 1 to 3 h after injection decreased by 75%, whereas the tumor retention was prolonged with Ga-68-FAPI-4 (25% washout). Regarding tumor-to-background ratios, at 1 h after injection both Ga-68-FAPI tracers performed equally. In comparison to F-18-FDG, the tumor uptake was almost equal (average SUVmax, 7.41 for F-18-FDG and 7.37 for Ga-68-FAPI-2; not statistically significant); the background uptake in brain (11.01 vs. 0.32), liver (2.77 vs. 1.69), and oral/pharyngeal mucosa (4.88 vs. 2.57) was significantly lower with Ga-68-FAPI. Other organs did not relevantly differ between F-18-FDG and Ga-68-FAPI. Conclusion: FAPI PET/CT is a new diagnostic method in imaging cancer patients. In contrast to F-18-FDG, no diet or fasting in preparation for the examination is necessary, and image acquisition can potentially be started a few minutes after tracer application. Tumor-to-background contrast ratios were equal to or even better than those of F-18-FDG.
Im Titel ist "68" hochgestellt
First published August 2, 2018
Gesehen am 04.04.2019